2007
DOI: 10.1291/hypres.30.1255
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Distribution of Salusin Expression in the Rat

Abstract: Salusin-and salusin-are multifunctional bioactive peptides with hypotensive and bradycardic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 9 publications
0
57
1
Order By: Relevance
“…Further, serum salusin-α levels may be reduced in hypertension, unlike the serum levels of urotensin-II, a similar peptide produced in endothelial cells (7). Modulators for the synthesis, release, and degradation of salusin-α still remain to be elucidated (11). In addition, the influence of antihypertensive drugs on serum salusin-α levels has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Further, serum salusin-α levels may be reduced in hypertension, unlike the serum levels of urotensin-II, a similar peptide produced in endothelial cells (7). Modulators for the synthesis, release, and degradation of salusin-α still remain to be elucidated (11). In addition, the influence of antihypertensive drugs on serum salusin-α levels has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit anti-salusin b (human) serum was obtained from Bachem (Bubendorf, Switzerland). The function of salusin b in rats was investigated by human salusin b and rabbit anti-salusin b (human) serum because human salusin b has been proved to be highly homologous to the rat salusin b [10,19]. Rabbit anti-salusin b (human) serum was diluted in 0.01 M PBS (1:400) for immunohistochemistry or 5 % goat serum (1:1000) for western blot.…”
Section: Salusin B and Anti-salusin B Serummentioning
confidence: 99%
“…Preprosalusin and its mRNA are widely expressed in both human tissues and rat tissues, including vasculature, central nervous system (CNS), lung and kidney [1][2][3]. Salusin b was also abundantly expressed in the CNS in both human and rats [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both are alternative splice products from preprosalusin, the torsion dystonia-related gene (TOR2A) [15]. The presence of preprosalusin in rat stomach tissue is specified in RTq-PCR studies [15,16]. A previous study reported the detection of salusin-α and salusin-β immunoreactivity in the stomach and in the intestines [17].…”
Section: Introductionmentioning
confidence: 99%